Designing for others: the roles of narrative and empathy in supporting girls' engineering engagement. Issue 3 (20th December 2021) - Peppler, Kylie; Keune, Anna; Dahn, Maggie; Bennett, Dorothy; Letourneau, Susan M.
Abstract : Purpose: Science museums provide a context for developing and testing engineering activities that support visitors in creating personally meaningful objects. This study aims to propose that narrative design elements in such engineering activities can foster empathy to support engineering engagement among girls ages 7–14. Design/methodology/approach: Taking a constructionist approach to engineering design, the authors present results from an observational study ( n = 202 girls) of engineering activities across three museums that were designed to foster girls' engineering engagement by integrating narrative elements aimed to foster empathy in activities. Using quantitative counts from observation protocols, the authors conducted statistical analyses to explore relationships between narrative, engineering and empathy. Findings: Linear regression demonstrated a statistically significant relationship between empathy and increased numbers of engineering practices within museum activities. Additionally, this led us to explore the impacts the potential narrative design elements may have on designing for empathy – multiple linear regressions found both narrative and empathy to be independently associated with engineering practices. Overall, the authors found that using narrative to design activities to elicit empathy resulted in girls demonstrating more engineering practices. Originality/value: The authors offer design ideas to foster aspects of empathy, including user-centered design, perspective-taking, familiarity and desire to help.